'Are women a priority?', 1947 (1947)
1947 1945-1960 "'Are women a priority?', 1947" [EP0086], 1947 In 1946, the Royal Commission on Equal Pay concluded tentatively that women in teaching and certain grades of the civil service might benefit from equal pay. Even these very limited proposals were rejected as inflationary by the Labour Government. In this article in the 13 June 1947 issue of Tribune, Jennie Lee appears to support that decision and argues that equal pay cannot be a priority during the post-war economic crisis. She also discusses the impact of the European Recovery Programme and Marshall Aid.